Advantages of a developmental psychopathology approach to studying the antecedents of physical health. Issue 1 (22nd June 2021) - Doom, Jenalee R.
Abstract: Although the field of developmental psychopathology has traditionally focused on mental health, there has been increasing interest in exploring how psychological and developmental factors are associated with physical health. I argue that the principles of developmental psychopathology may be particularly useful for understanding physical health across development. I discuss how researchers can apply the following developmental psychopathology principles to the study of physical health: (a) dimensional measurement of stress exposure, (b) the multifaceted nature of risk and resilience, (c) focus on processes and pathways, and (d) lifespan development and intergenerational effects. I provide several future directions and considerations for work in this area, many of which are consistent with the new goals of Infant and Child Development .